Genetic background of supernumerary teeth - Subasioglu, Asli (Eur J Dent, 2015)
Supernumerary teeth (ST) are odontostomatologic anomaly characterized by as the existence excessive number of teeth in relation to the normal dental formula. This condition is commonly seen with several congenital genetic disorders such as Gardner's syndrome, cleidocranial dysostosis and cleft lip and palate. Less common syndromes that are associated with ST are; Fabry Disease, Ellis-van Creveld syndrome, Nance-Horan syndrome, Rubinstein-Taybi Syndrome and Trico–Rhino–Phalangeal syndrome. ST can be an important component of a distinctive disorder and an important clue for early diagnosis. Certainly early detecting the abnormalities gives us to make correct management of the patient and also it is important for making well-informed decisions about long-term medical care and treatment. In this review, the genetic syndromes that are related with ST were discussed.